Soil Organic Carbon Quantity and Distribution in Frost Boils in a Canadian High Arctic Polar Semi-desert Ecosystem - Muller, Amanda (2021)
High Arctic soil organic carbon (SOC) stores are a key component in the global C cycle and are locally important for nutrient cycling in the polar deserts that dominate these regions. Compared to other Arctic regions, we know relatively little about the quantity and distribution of polar desert SOC. Unique frost-driven soil processes in polar deserts result in patterned ground features such as frost boils wherein, SOC-rich patches may develop via diapirism. The objective of this research was to determine whether these patches act as important nutrient sources for vascular plants and how subsurface patches of SOC associated with diapirism contribute to the polar desert carbon pool. I investigated SOC in 560 frost boils across two polar semi-deserts in the Canadian High Arctic using a field portable visible and near-infrared spectrophotometer. I found frequency of subsurface SOC patches was linked to broad differences in vegetation community. To determine if diapirs provide an enhanced source of plant-available nutrients we used natural abundance and enriched isotope 15N techniques to trace the flow of N through the soil-plant system. When diapir patches were available, the dominant deciduous shrub Salix arctica increased its subsurface (i.e., diapir) N uptake, often had greater % cover, and plant root biomass doubled within-diapir. Plant uptake of enriched 15N injected into C-rich soil patches was 2.5 fold greater in diapir than in non-diapir frost boils, also confirming that S. arctica is able to access N when these patches are present. My best estimate of SOC stored in the active layer of High Arctic polar semi-deserts is 8.14 ± 0.45 Pg SOC, or ~73% of SOC stored in the top 30 cm of all High Arctic soils. When subsurface SOC patches were detected in frost boils, those frost boils contained nearly double the SOC compared to those without patches and on average 40% of the SOC was found within the patch. Thus, despite diapiric frost boils representing only 35% of frost boils, they contribute disproportionately to ...